Analisis faktor demografi dan big five personality terhadap literasi keuangan pengusaha usaha mikro, kecil dan menengah kota Tasikmalaya - Azizah Fauziyah; T. Koeswandi; S. Sarah (Journal of Business Management Education (JBME), 2020)
This study aims to determine the effect of demographic factors and big five personality on the financial literacy of UMKM entrepreneurs in Tasikmalaya City. In addition, researchers can find out how the description of the financial literacy of SMEs entrepreneurs in the City of Tasikmalaya so that researchers can formulate solutions for low levels of financial literacy. This study used a quantitative descriptive method, data were collected through an interview process using a closed questionnaire to 30 Tasikmalaya SMEs entrepreneurs who had just started a business ≥ 5 years. By using multiple regression analysis, the researcher found that partially, only demographic factor variables have a significant effect on financial literacy. Simultaneously, demographic factors and big five personality have a significant influence on financial literacy.